DAYA MULTIPLIKASI EKSPLAN KENTANG AR 8 PADA BERBAGAI KONSENTRASI BENZIL AMINO PURIN (BAP) DAN EKSTRAK BAWANG MERAH DALAM MEDIA DASAR MURASHIGE DAN SKOOG (MS) SECARA IN VITRO - Numba, Sudirman; Abdullah, Abdullah; Ridwan, Rahmat (Percetakan Umi Toaha Makassar, 2024)
The technique of propagating potato seeds through tissue culture has long been used to produce quality and disease-free seeds. This study aims to test the effect of the combination of BAP and Shallot Extract on the growth of potato plant explants on MS media (Murshige & Skooge). Research in experimental form uses a completely randomized design (CRD) in a factorial pattern consisting of two factors. As the first factor, the growth hormone BAP consists of 4 levels, namely: 0 ppm, 2 ppm, 3 ppm and 4 ppm. Meanwhile, the second factor is: shallot extract consists of 4 treatment levels, namely: 0%, 0.2%, 0.4% and 0.6%. Thus, there were 16 treatment combinations which were repeated 6 times so that the total experimental units were 96. The ABA treatment with a concentration of 2 ppm/liter gave the best effect on the shoot formation time and root formation time of AR 8 potato plant explants. However, the treatment without ABA had a good effect on Shoot length and root length of explant potato plant varieties AR 8. Shallot extract treatment with a concentration of 20% had the best effect on shoot formation time, root formation time, shoot length and number of leaves. However, the treatment with a concentration of 40% had a better effect on the parameters of the number of shoots and the number of explant segments of the AR 8 variety of potato plants. The interaction of the ABA treatment with a concentration of 2 ppm and the shallot extract with a concentration of 20% had the best effect on the time of emergence of shoots and roots on the AR 8 Potato Explants. However, the interaction without ABA (0ppm) and shallot extract had a better effect on the parameters of shoot length, number of leaves, and number of explant segments in the AR 8 potato variety.